Reductions in training load and dietary carbohydrates help restore health and improve performance in an Ironman triathlete - Maffetone, P. B.; Laursen, P. B. (International Journal of Sports Science & Coaching, 2017)
While most endurance athletes and coaches recommend higher training loads and high-carbohydrate low-fat diets, some studies report benefits of lower intensity training for performance improvements and a low-carbohydrate high-fat eating plan. We present the case of a 38-year-old female professional/elite Ironman triathlete who presented with decreased performances, alongside severe gastrointestinal distress, excess fatigue, and severe daytime hunger. Training load was reduced from 30 to 18 h before a gradual increase to 24 h. Dietary recommendations included reducing carbohydrate and increasing dietary fat intake. Over a six-week period, daily carbohydrate content was gradually decreased from 73% (475 g) to 12% (78 g) of total calories, while fat content increased from 14% (40 g) to 75% (217 g), and protein levels remained constant at 13% (85 g). Within two months, the athlete reported increased perception of daily energy during and between training sessions, less perceived hunger and fatigue, and reduced need for daytime naps. Cycling power output increased by 20 W and run pace increased (12-15 s km-1) at the same training heart rate (141 beat min-1), and with the exception of water, nutrition was no longer required during long duration training (~4 h). Race calories consumed were reduced from ~400 kcal h-1 in previous years to ~175, 145, and 130 kcal h-1 over the course of the next three Ironman events. Signs and symptoms of gastrointestinal stress ceased to occur, and two of three races were personal best times, with the final event completed in 8 h 52 min. We conclude that reducing training load, and dietary carbohydrates and increasing dietary fat, markedly improved a variety of health functions, reduced exogenous nutrient requirements during training and racing, and increased performance in an elite triathlete. ABSTRACT FROM AUTHOR